LAND MANAGEMENT IN YOGYAKARTA SPECIAL REGION - Iqbal, Muhammad; Pratiwi, Vindhi Putri (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2020)
DIY As a special autonomous region, it has the right to manage land in DIY where not everyone can directly patent land in DIY. Land management in DIY sometimes becomes polemic for the community. The research method carried out is a qualitative method. Data collection techniques in this study were interviews with relevant stakeholders such as the Department of Land and Spatial DIY and the National Land Agency of the DIY and literature study, namely data collection using various literature and legal documents governing land management in DIY. Land management which is divided into two previously mentioned, namely Keprabon Land and Non-Keprabon Land or Dede Keprabon which are found in all regions in DIY. The Sultanate and the Pakualaman of Pakualaman are legal subjects for land ownership in DIY. Besides, the Sultanate is also given the authority to be able to manage the land of Keprabon and non-Keprabon land in DIY. In this case, all forms of management, use of private land, all kinds of business, social, legal and others have been regulated through Article 33 Paragraph (4) of the Privileges Law. Special Autonomy makes this area has rights to land management where DIY has four boundaries divided into Sultan Ground (SG) land, Pakualaman Ground (PG), village land and DIY land. The granting of authority over the use of Sultanate land and Pakualaman land is carried out following applicable legal provisions, namely according to customary law.